Pendampingan Penyampaian SPT Tahunan PPh Melalui Program Relawan Pajak Di Kantor Pelayanan Pajak Pratama Pondok Aren - Wardana, Arief Budi; Supriyadi; Trisulo (Jurnal Abdi Mandala, 2024)
Formal tax compliance through the submission of Annual Income Tax Returns needs to be improved to support the achievement of tax revenue targets. Even though the government provides a convenient way of reporting annual income tax returns using e-filling, many taxpayers still do not report tax returns due to a lack of understanding of how to utilize this tool. The Tax Volunteer Program, which is a collaboration between DJP and universities, is a solution to assist taxpayers in reporting tax returns. The community service team's mentoring process was carried out at KPP Pratama Pondok Aren using e-filling. As a result, many taxpayers have obtained Electronic Proof of Receipt as proof that formal obligations have been fulfilled while reducing service queues at KPP Pratama Pondok Aren as the end of the Annual Income Tax Return reporting period approaches.